2014
DOI: 10.1002/adom.201400083
|View full text |Cite
|
Sign up to set email alerts
|

Optically Pumped Lasing from Single Crystals of a Cyano‐Substituted Thiophene/Phenylene Co‐Oligomer

Abstract: Room temperature optically pumped lasing is achieved for a new n-type molecular crystal of 2,5-bis(4′-cyanobiphenyl-4-yl)­thiophene (BP1T-CN). Efficient stimulated emission in the Fabry–Pérot crystal cavity is supported with a high group refractive index (4.18–4.98), Q factor (910–1860), material gain coefficient (120 cm-1), and a high stimulated emission rate demonstrated by pump–probe measurements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 27 publications
1
48
0
Order By: Relevance
“…Therefore, we should use TPCO crystals having a lying molecular orientation which enables surface emission from the crystal face. Among a variety of TPCO derivatives, we found that cyano‐substituted TPCOs satisfy this condition, and their single crystals show polaritonic characteristics in the VCSELs . In this section, we present angle‐resolved and time‐resolved spectroscopy measurements to demonstrate the polariton formation and discuss them in relation to cooperative behaviors mentioned in the previous sections.…”
Section: Polaritonic Emission From Microcavity Structures With Tpco Cmentioning
confidence: 75%
“…Therefore, we should use TPCO crystals having a lying molecular orientation which enables surface emission from the crystal face. Among a variety of TPCO derivatives, we found that cyano‐substituted TPCOs satisfy this condition, and their single crystals show polaritonic characteristics in the VCSELs . In this section, we present angle‐resolved and time‐resolved spectroscopy measurements to demonstrate the polariton formation and discuss them in relation to cooperative behaviors mentioned in the previous sections.…”
Section: Polaritonic Emission From Microcavity Structures With Tpco Cmentioning
confidence: 75%
“…After these achievements many organic semiconductors including TPCOs were reported to exhibit laser oscillation in the form of a single crystal . Peculiar crystallographic structures of TPCOs are responsible for it . In TPCO crystals the molecules are aligned either vertically or horizontally to the bottom (wide) crystal plane.…”
Section: Laser Oscillation From a Thin Single Crystalmentioning
confidence: 99%
“…14 Optically pumped lasing has already been reported for single crystals of 2,5-bis(4 -cyanobiphenyl-4-yl)thiophene (BP1T-CN). 15 In this work, we fabricate heterojunction-type OLEDs using TPCO derivatives having a molecular framework of 5,5 -bis (4-biphenylyl)-2,2 -bithiophene (BP2T) which consists of biphenyl-capped bithiophene. This unsubstituted BP2T was chosen as a p-type while cyano-substituted BP2T, 5,5 -bis (4 -cyanobiphenyl-4-yl)-2,2 -bithiophene (BP2T-CN), was used as n-type.…”
Section: Introductionmentioning
confidence: 99%